HISTORY OF FORMATION AND CURRENT STATE OF INFORMATION RETRIEVAL TECHNOLOGY OSINT - Zhmur, Nataliia; Zemlianikina, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: defining the concept of OSINT as a technology for finding and using information from open sources, revealing the meaning, value, and essence of such a concept as «open source intelligence», as well as researching historical aspects and providing insights into the prospects of using OSINT technology. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, intersectoral method of legal research, historical, cognitive-analytical, etc. Results: addressing the historical stages of the formation of OSINT will provide an opportunity to improve the technology of search and use of information from open sources without violating the law. Discussion: based on the researched data the historical aspects of OSINT development and perspectives of the modern use of technology as one of the ways to obtain intelligence, NATO’s experience in implementing technology in global intelligence, characterization, and analysis of intelligence value of open sources are analyzed. The role and value of intelligence technology from open sources of information «OSINT» is indisputable. Since the topic is not comprehensively researched, experts cannot come to a common opinion on the question: «What percentage of intelligence is obtained precisely from open sources of information?». Some estimate that 35 to 95 percent of the intelligence is collected, while the share of OSINT spending in the U.S. intelligence budget is about 1 percent. Another opinion is that the indicator is stable and equal to about 80%. This technique emerged relatively recently and has not yet been widely used in various countries of the world. But already quite a large number consider this concept powerful and perhaps one of the most promising means of intelligence for the future.